Survei Tingkat Kebugaran Jasmani (VO2maks) Pemain Club Persatuan Bulu Tangkis Se Kecamatan Lais Kabupaten Musi Banyuasin - M. Ruli Nanda; Hengki Kumbara; Husni Fahritsani (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Initial observations found fitness problems which resulted in the poor performance of players at badminton association clubs in Lais District, Musi Banyuasin Regency. The aim of this research was to determine the fitness level (VO2max) of badminton association club players in Lais District, Musi Banyuasin Regency. The method used in the research approach is the survey method. The test instrument uses a multistage test (bleep test). Data analysis uses percentage analysis. The test results at PB Lais Jaya showed that two players had low VO2max criteria, 7 players had medium criteria VO2max, 3 players had quite good VO2max criteria and no players had good and high VO2max criteria. Meanwhile, PB Mitra Ernest explained that 1 player had a low VO2max criterion, 1 player had a medium VO2max criterion, 3 players had a fairly good VO2max criterion, 1 player had a good criterion and no player had a good and high VO2max criterion. The fitness results of all badminton players in Lais District can be classified as having a moderate level of fitness because based on the test results it can be seen that the average VO2max of athletes is in the interval 25-33% at level 31 while the lowest fitness value (VO2max) is 22.5 with low criteria, the highest fitness value (VO2max) is 43.6 with good criteria.